A Measure of the Potential Impact of Hospital Community Health Activities on Population Health and Equity. Issue 5 (September 2018) - Begun, James W.; Kahn, Linda M.; Cunningham, Brooke A.; Malcolm, Jan K.; Potthoff, Sandra
Abstract : Context: Many hospitals in the United States are exploring greater investment in community health activities that address upstream causes of poor health. Objective: Develop and apply a measure to categorize and estimate the potential impact of hospitals' community health activities on population health and equity. Design, Setting, and Participants: We propose a scale of potential impact on population health and equity, based on the cliff analogy developed by Jones and colleagues. The scale is applied to the 317 activities reported in the community health needs assessment implementation plan reports of 23 health care organizations in the Minneapolis-St Paul, Minnesota, metropolitan area in 2015. Main Outcome Measure: Using a 5-point ordinal scale, we assigned a score of potential impact on population health and equity to each community health activity. Results: A majority (50.2%) of health care organizations' community health activities are classified as addressing social determinants of health (level 4 on the 5-point scale), though very few (5.4%) address structural causes of health equity (level 5 on the 5-point scale). Activities that score highest on potential impact fall into the topic categories of "community health and connectedness" and "healthy lifestyles and wellness." Lower-scoring activities focus on sick or at-risk individuals, such as the topic category of "chronic disease prevention, management, and screening." Health care organizations in the Minneapolis-St Paul metropolitan area vary substantially in the potential impact of their aggregated community health activities. Conclusions: Hospitals can be significant contributors to investment in upstream community health programs. This article provides a scale that can be used not only by hospitals but by other health care and public health organizations to better align their community health strategies, investments, and partnerships with programming and policies that address the foundational causes of population health and equity within the communities they serve. Abstract : Supplemental Digital Content is Available in the Text.